Buscando prevenir a reinternação para preservar-se do sofrimento: a família frente ao processo de recuperação da criança após a alta hospitalar - Pinto, Júlia Peres [UNIFESP] (2010)
The recovery process, concerning the experience lived by the family of the hospitalized, has been the subject of few research projects to date. The present study aimed to understand the meaning that the family attributes to their experience in the recovery process of a child suffering from an acute illness after a hospital discharge and to design a theoretical model about this experience. The Symbolic Interactionism and the Grounded Theory were used as the theoretical and the methodological frameworks, respectively. Data collection was carried out by means of interviews and participant-observation with eleven families. Concepts produced by comparative data analysis revealed two interactive processes. The first of them, Mobilizing oneself to restore the balance of family functioning, depicts family interactions which favor their adaptation after the impact and disarray caused by the child’s hospitalization. The second, Suffering with the possibility of having to rehospitalize the child, expresses the aspects that cause suffering to the family and that compromise family adaptation, jeopardizing restoration of their balance. The Theoretical Model TRYING TO PREVENT THE CHILD’S REHOSPITALIZATION TO PRESERVE FAMILY INTEGRITY, is part of the concepts emerging from data analysis and shows that the effects of illness and hospitalization may continue to be felt in the family functioning and to produce suffering even after the child’s hospital discharge and recovery. This takes place because the family is still shaken and remains alert so as to identify early changes in the child’s health that may point to a relapse and consequent possibility of rehospitalization.